Boffin Boy and the monsters of the deep - Orme, David, 1948 Mar. 1-; Richardson, Peter (Watlington, Oxon : Ransom Publishing, 2006)
Fourteen-year-old science geek Rick Shaw becomes his alter ego, the superhero Boffin Boy, in order to stop a giant mutant jellyfish from stealing all the chocolates and sweets it can find.
2.3
3-6
Keywords: Good and evil -- Comic books, strips, etc. -- Juvenile fiction; Heroes -- Comic books, strips, etc. -- Juvenile fiction; Cartoons and comics; Good and evil -- Fiction; Heroes -- Fiction; Science fiction; Comic books, strips, etc; Good and evil -- Comic books, strips, etc. -- Fiction; Heroes and heroines -- Comic books, strips, etc. -- Fiction; Science fiction comic books, strips, etc; Superhero comic books, strips, etc; Graphic novels; Science fiction comic books, strips, etc; Superhero comic books, strips, etc